(untitled) - Dickens, Charles (Book-of-the-Month Club, 1998)
Relates the adventures of a young Englishman who gives his life during the French Revolution to save the husband of the woman he loves.
7-A.
Keywords: Fiction; War stories; History; Paris (France); History; London (England)